Влияние населения эпохи палеолита на териофауну Среднего Приднестровья - Татаринов, К.А. (Вестник зоологии, 1993)
Critical role of the palaeolithic hunters in game mammal fauna reduction is established in the following sequence: the mammoth, the equid-rangifer faunal complexes extermination.